Using Heuristic and Branch and Bound Methods to Solve a Multi-Criteria Machine Scheduling Problem - Jawad, Aseel Aboud; Ali, Faez Hassan; Hasanain, Wafaa Sayyid (Iraqi Journal of Science, 2020)
In this paper, we investigate some methods to solve one of the multi-criteria machine scheduling problems. The discussed problem is the total completion time and the total earliness jobs To solve this problem, some heuristic methods are proposed which provided good results. The Branch and Bound (BAB) method is applied with new suggested upper and lower bounds to solve the discussed problem, which produced exact results for in a reasonable time.